Risk Aversion, Time Preference and Cross-border Commuting and Migration Intentions - Klaus Nowotny (Austrian Institute of Economic Research (WIFO), 2010)
This paper analyses the effect of individual risk aversion and time preference on cross-border commuting and migration intentions. Both the theoretical and empirical results show that the probability of being willing to migrate decreases with risk aversion, the rate of time preference, and the maximum number of periods an individual can work abroad. The probability of being willing to commute also decreases with risk aversion, but at a smaller rate compared to the willingness to migrate, while it is (largely) unaffected by intertemporal consumption preferences. The analysis helps to shed more light on the role of time preference and risk aversion as determinants of mobility decisions, which is especially important for integrating regions where both migration and commuting are possible, as in the enlarged European Union.
Keywords: 330; Internationale Migration; Motivation; Risikoaversion; Intertemporale Entscheidung; Diskontierung; EU-Staaten